2012
DOI: 10.1371/journal.pone.0049149
|View full text |Cite
|
Sign up to set email alerts
|

The Single T65S Mutation Generates Brighter Cyan Fluorescent Proteins with Increased Photostability and pH Insensitivity

Abstract: Cyan fluorescent proteins (CFP) derived from Aequorea victoria GFP, carrying a tryptophan-based chromophore, are widely used as FRET donors in live cell fluorescence imaging experiments. Recently, several CFP variants with near-ultimate photophysical performances were obtained through a mix of site-directed and large scale random mutagenesis. To understand the structural bases of these improvements, we have studied more specifically the consequences of the single-site T65S mutation. We find that all CFP varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Cerulean3 shows high photostability and reduced photoswitching behavior, a high quantum yield of 0.87, and only a slightly reduced absorption coefficient compared to Cerulean. Reversing only S65T stabilized the H-bonding status of the hydroxyl group and resulted in a Cerulean with increased photostability and pH-resistance, high quantum yield, and reduced reversible photoswitching (Fredj et al, 2012). …”
Section: Fluorescent Proteins For Fretmentioning
confidence: 99%
“…Cerulean3 shows high photostability and reduced photoswitching behavior, a high quantum yield of 0.87, and only a slightly reduced absorption coefficient compared to Cerulean. Reversing only S65T stabilized the H-bonding status of the hydroxyl group and resulted in a Cerulean with increased photostability and pH-resistance, high quantum yield, and reduced reversible photoswitching (Fredj et al, 2012). …”
Section: Fluorescent Proteins For Fretmentioning
confidence: 99%
“…We first determined the emission spectra of CyPet under different pH conditions. We found that the emission spectra of CyPet at pH 5.2 exhibited double emission peaks at 464 nm and 480 nm as some other CFPs [10,14]. Under conditions of neutral pH (pH 7.0), we show that this double emission peak converts to a single emission peak, positioned at 474 nm.…”
Section: Comparison Of the Cypet Crystal Structure Under Different Phmentioning
confidence: 58%
“…We found that the emission spectra of CyPet at pH 5.2 exhibited double emission peaks at 464 nm and 480 nm as some other CFPs [10,14]. We found that the emission spectra of CyPet at pH 5.2 exhibited double emission peaks at 464 nm and 480 nm as some other CFPs [10,14].…”
Section: Comparison Of the Cypet Crystal Structure Under Different Phmentioning
confidence: 66%
“…The homogeneous lifetime decay seen for the Rhacostoma FP may be desirable for fluorescence‐lifetime imaging microscopy (FLIM)‐based energy transfer studies. Much effort has been placed on improving the CFP for energy transfer studies, part of which was the development of homogeneous lifetime decays , although the shapes of the emission spectra were essentially unchanged. Another potential energy donor to the YFP is the teal FP (TFP) , having excitation and emission peaks close to the Rhacostoma FP peaks.…”
Section: Discussionmentioning
confidence: 99%